Innovation through portuguese aeronautical heritage - Pires, Raquel Rico Mendes Palhais (2015)
Tourism has been challenged by specialised and segmented consumers, which aim to diversify and enrich their experiences portfolio with distinctive products consumption, combining different services to ensure their whole travel expedition. Besides, tourism products have global competitors. Hence their constant differentiation is critical to guarantee their success. However, tourism sector is dominated by micro and small enterprises, which could compromise their innovation capability and new products development. Therefore, firms’ collaboration, appealing at innovation networks framework, have to be profusely applied in the tourism sector once it develops synergies, reduces costs, increases promotion, promotes knowledge creation and spreads out ideas generation. Despite the growth in tourism literature, most innovation networks research is applied in technological sectors. This study intends to analyse the development of a tourism product that values Portuguese aeronautical resources, considering a management model that enables continuous product adaptions/ creations that satisfies the changing demand. This research aims to contribute to improve the state of the art through the development of knowledge in two different (and new) integrated research domains: i) explores the civil and military aeronautical heritage as a tourism resource to constitute a route through Portugal, where these assets exploration as a route all over the country could gain international relevance; ii) supports a tourism product management with the absorption of innovation networks frameworks. As research results, the Portuguese Aeronautical Route addresses study goals and proposes a non-traditional product that could qualify Portuguese touristic offer. It is an opportunity to promote the country as an aeronautical destination brand, supported by a multidestination route. Thus, a network combined with a route’s framework enables a continuous resources valorisation and ensures sustainability by appealing at multiple organizations collaboration, which feeds innovation cycle and reinforces its strategy through its processes and marketing domains